2015
DOI: 10.1021/acs.cgd.5b00427
|View full text |Cite
|
Sign up to set email alerts
|

From Two-Dimensional Layers to Three-Dimensional Frameworks: Expanding the Structural Diversity of Uranyl Compounds by Cation–Cation Interactions

Abstract: Two uranyl tungstates, Cs 4 [(UO 2 ) 4 (WO 5 )-(W 2 O 8 )O 2 ] (CsUW-1) and Cs 4 [(UO 2 ) 7 (WO 5 ) 3 O 3 ] (CsUW-2), were obtained via the high-temperature solid-state synthesis method by reacting uranyl nitrate with WO 3 in the presence of cesium nitrate. CsUW-1 crystallizes in space group P2 1 /n, adopting a two-dimensional (2D) sheet structure. CsUW-2 forms a three-dimensional (3D) framework constructed by complex 2D sheets linked by cation−cation interactions of UO 2 2+ groups. The cation−cation interacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 49 publications
0
15
0
Order By: Relevance
“…Cation-cation interactions cause the uranyl bond engaged in this interaction to weaken and the ν 1 band to red shift. Xiao et al [118] reported Raman spectra of the two uranyl tungstate compounds, Cs 4 [(UO 2 ) 4 (WO 5 )W 2 O 8 )O 2 ] and Cs 4 [(UO 2 ) 7 (WO 5 ) 3 O 3 ]. These compounds contain cation-cation interactions in four of the seven crystallographically unique U(VI) polyhedra.…”
Section: Chemical and Structural Elucidation Of Uranium Solid-state Cmentioning
confidence: 99%
See 1 more Smart Citation
“…Cation-cation interactions cause the uranyl bond engaged in this interaction to weaken and the ν 1 band to red shift. Xiao et al [118] reported Raman spectra of the two uranyl tungstate compounds, Cs 4 [(UO 2 ) 4 (WO 5 )W 2 O 8 )O 2 ] and Cs 4 [(UO 2 ) 7 (WO 5 ) 3 O 3 ]. These compounds contain cation-cation interactions in four of the seven crystallographically unique U(VI) polyhedra.…”
Section: Chemical and Structural Elucidation Of Uranium Solid-state Cmentioning
confidence: 99%
“…Substantial elongation of the uranyl bonds (1.805–1.821 Å) is observed with Cs 4 [(UO 2 ) 4 (WO 5 )W 2 O 8 )O 2 ] while there is more variability (1.76–1.99 Å) for Cs 4 [(UO 2 ) 7 (WO 5 ) 3 O 3 ]. Concurrently, the Raman spectra reveal two uranyl vibrational modes [118]. The first is located at 828 cm −1 for unperturbed uranyl bonds and a red shifted mode between ~780 and 760 cm −1 for the uranyl oxo bonds engaged in cation-cation interactions.…”
Section: Chemical and Structural Elucidation Of Uranium Solid-state Cmentioning
confidence: 99%
“…Cation-cation interactions have been found to extend this dimensionality: selected examples include [UO2(NO2TA)2(H2O)] (NO2TA = 2-nitroterephthalic acid) 7 or the purely inorganic Cs4[(UO2)7(WO5)3O3]. 8 More recently the supramolecular chemists arsenal of non-covalent interactions have featured in uranyl crystal chemistry. Hydrogen bonding between a [UO2Cl4] 2anion and bipyridinium cations afford various topologies according to the nature of the cation.…”
Section: Introductionmentioning
confidence: 99%
“…The Raman spectrum of K 4 (UO 2 ) 2 Si 8 O 20 ·4H 2 O in the 100–3600 cm –1 region is shown in Figure and exhibits a strong peak at 781 cm –1 , which corresponds to the symmetric ν 1 mode of (UO 2 ) 2+ cations (Table S4). Another shoulder at 751 cm –1 is also attributed to the ν 1 (UO 2 ) 2+ vibrations. , The ν 3 modes of (UO 2 ) 2+ ions can be found at 813 cm –1 , , and the ν 2 (UO 2 ) 2+ modes are located at 223 and 297 cm –1 . The Raman spectrum in the range of 400–700 cm –1 and high frequency range of 950–1100 cm –1 illustrates a large number of peaks owing to the existing of complex oxo-silicate fragments in the structure.…”
Section: Resultsmentioning
confidence: 90%
“…35 Another shoulder at 751 cm −1 is also attributed to the ν 1 (UO 2 ) 2+ vibrations. 35,36 The ν 3 modes of (UO 2 ) 2+ ions can be found at 813 cm −1 , 36,37 and the ν 2 (UO 2 ) 2+ modes are located at 223 and 297 cm −1 . 38 The Raman spectrum in the range of 400−700 cm −1 and high frequency range of 950−1100 cm −1 illustrates a large number of peaks owing to the existing of complex oxo-silicate fragments in the structure.…”
Section: Resultsmentioning
confidence: 93%